REKONSEPTUALISASI ETIKA PESERTA DIDIK DALAM MENUNTUT ILMU AL-QUR’AN DI ERA 4.0 - Uswatun Hasanah; Kurfati Aminun; Nor Rochmatul Wachidah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2022)
Education in the period of industrial revolution faces various issues, including the student’s ethical issues as the transformation of learning becomes digital-based implementation. Therefore, it is necessary to reassess the basic foundations of the Islamic view of the student’s ethics, especially concerning about studying Qur'an. This study aims to examine and re-conceptualize the ethics of students in studying the Qur'an in the industrial revolution of 4.0. This research is a library research with documentation as the main data collection technique. The data analysis method used in this research is content analysis. The results of this study reveal that the ethics of students in traditional concepts include efforts to purify the soul from bad intentions and despicable traits, be kind to other students, be persistent or high-spirited in seeking knowledge, choose good teachers and respect their expertise, and be consistent in Qur’an memorization. These ethics are very relevant when being implemented for studying the Qur'an in the 4.0 era. However, such ethical concepts need to be developed according to current needs and conditions by strengthening commitment, implementing communication ethics, digital literacy and respects in using digital Qur'an applications in reading and memorizing the Qur'an. By integrating the concept of traditional ethics with modern ethics in the learning process, it is expected to provide more optimal and effective results in studying the Qur'an in the 4.0 era.